Сюрприз с дыркой от бублика: [роман] / Наталья Александрова - Александрова Наталья Николаевна (Следствие ведут: Лола и Маркиз, 2016)
Экземпляры: аб. (20240222) / Инвентарный номер: 64490 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: А 46 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44